(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research article, the development of a stable & secured energy efficient cooperative multi-path routing protocols for the WSNs using rejuvenated double stage cooperative multi-path routing protocols for effective transfer of data packets, to increase the network’s life-time and minimize the consumption of the energy, which is one of the proposed objectives. Here, design & development of an energy efficient dual stage cooperative routing protocol (DSCR) in multi-hop wireless networks maximizing the network lifetime, increasing the reliability and minimize the energy consumption, is being portrayed. The main objective of this article is to present an improvised / rejuvenated version of the dual stage data transfer scheme that computes the routing path by using cooperative mechanisms using the concept of reduced energies of the nodes. The work done is also compared with the work done by other authors in order to substantiate the effectiveness of the algorithm developed. This objective also demonstrates the various results obtained for all the test cases along with the necessary observations and explanations in the form of discussions and diagrammatic representations.